Variola Virus Topoisomerase: DNA Cleavage Specificity and Distribution of Sites in Poxvirus Genomes - Minkah, Nana (2007)
Topoisomerase enzymes regulate superhelical tension in DNA resulting from transcription, replication, repair, and other molecular transactions. Poxviruses encode an unusual type IB topoisomerase that acts only at conserved DNA sequences containing the core pentanucleotide 5′-(T/C)CCTT-3′. In X-ray structures of the variola virus topoisomerase bound to DNA, protein-DNA contacts were found to extend beyond the core pentanucleotide, indicating that the full recognition site has not yet been fully defined in functional studies. Here we report quantitation of DNA cleavage rates for an optimized 13 bp site and for all possible single base substitutions (40 total sites), with the goals of understanding the molecular mechanism of recognition and mapping topoisomerase sites in poxvirus genome sequences. The data allow a precise definition of enzyme-DNA interactions and the energetic contributions of each. We then used the resulting “action matrix” to show that favorable topoisomerase sites are distributed all along the length of poxvirus DNA sequences, consistent with a requirement for local release of superhelical tension in constrained topological domains. In orthopox genomes, an additional central cluster of sites was also evident. A negative correlation of predicted topoisomerase sites was seen relative to early terminators, but no correlation was seen with early or late promoters. These data define the full variola virus topoisomerase recognition site and provide a new window on topoisomerase function in vivo.